2021
DOI: 10.3390/jcm11010138
|View full text |Cite
|
Sign up to set email alerts
|

Does Time to Theatre Affect the Ability to Achieve Fracture Reduction in Tibial Plateau Fractures?

Abstract: Surgical management of displaced tibial plateau fracture (TPF) is often delayed due to accompanying soft tissue injuries sustained at the time of injury. The primary aim of this study was to assess the effect of time to surgery on fracture reduction in cases of TPF. The secondary aim was to assess the effect of preoperative demographics and residual articular step on Lysholm Scores and Knee Injury and Osteoarthritis Outcome Scores (KOOS) following fixation. Patients between 2006 and 2017, managed by a single s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Although the rate of deep SSI in this series was relatively high, it is comparable with previously reported deep SSI rates after ORIF from the same institution [10.3% (41/396)], the 2 aforementioned studies investigating acute fixation, and previous rates associated with staged protocols (5.0%-14.2%). 13,17,26 The rate of reoperation after tibial plateau fixation has historically been high, even with delayed fixation. Egol et al 13 reported a reoperation rate of 16% among 52 patients with Schatzker VI fractures undergoing delayed fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the rate of deep SSI in this series was relatively high, it is comparable with previously reported deep SSI rates after ORIF from the same institution [10.3% (41/396)], the 2 aforementioned studies investigating acute fixation, and previous rates associated with staged protocols (5.0%-14.2%). 13,17,26 The rate of reoperation after tibial plateau fixation has historically been high, even with delayed fixation. Egol et al 13 reported a reoperation rate of 16% among 52 patients with Schatzker VI fractures undergoing delayed fixation.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[15][16][17] Although recent case series have supported the safety of acute fixation, there remain limited comparative studies investigating the safety of acute versus delayed ORIF of these fractures. 3,[15][16][17][18][19][20] The purpose of this study was to evaluate if utilization of an acute ORIF protocol at a single level 1 trauma center affected the incidence of wound complications in a cohort of patients with high-energy Schatzker IV/V/VI tibial plateau fractures. In addition, we aimed to examine the financial implications of these 2 treatment strategies by comparing total operative costs and hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of many orthopaedic fractures, both operatively and nonoperatively, requires timeliness to allow for appropriate reduction and maintenance of alignment to allow for healing. Delays in treatment can result in changes to management, malunion, and increased complications 5–9…”
Section: Introductionmentioning
confidence: 99%
“…Delays in treatment can result in changes to management, malunion, and increased complications. [5][6][7][8][9] The goals of this study were to characterize the volume of ambulatory orthopaedic fractures that presented to a clinic and the emergency room immediately after the initial implementation of social distancing practices. The authors hypothesized that there would be an overall increased delay in care for ambulatory orthopaedic fracture patients during the early COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%